2014
DOI: 10.1016/j.biomaterials.2013.10.079
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced GLT-1 mediated glutamate uptake and migration of primary astrocytes directed by fibronectin-coated electrospun poly-l-lactic acid fibers

Abstract: Bioengineered fiber substrates are increasingly studied as a means to promote regeneration and remodeling in the injured central nervous system (CNS). Previous reports largely focused on the ability of oriented scaffolds to bridge injured regions and direct outgrowth of axonal projections. In the present work, we explored the effects of electrospun microfibers on the migration and physiological properties of brain astroglial cells. Primary rat astrocytes were cultured on either fibronectin-coated poly-l-lactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 51 publications
1
114
0
Order By: Relevance
“…4). Nanostructured topographical features can increase astroglial ATP release 209 , downregulate GFAP expression 210 , and increase the expression of glutamate transporters and the clearance of extracellular glutamate 211 . Stiffer substrates have been associated with the activation of microglia (amoeboid morphology, upregulation of CD11b) and of astrocytes (hypertrophy, upregulation of GFAP), as well as their proliferation, migration and adhesion 158 .…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
“…4). Nanostructured topographical features can increase astroglial ATP release 209 , downregulate GFAP expression 210 , and increase the expression of glutamate transporters and the clearance of extracellular glutamate 211 . Stiffer substrates have been associated with the activation of microglia (amoeboid morphology, upregulation of CD11b) and of astrocytes (hypertrophy, upregulation of GFAP), as well as their proliferation, migration and adhesion 158 .…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
“…Moreover, although some authors did not find significant alterations in astrocyte activation when cells were seeded on a fibrous surface in comparison with cells cultured on flat solvent-cast films (assessed in terms of glial fibrillary acidic protein (GFAP) and vimentin protein expression) [14], others claimed that the contact of astrocytes with fibres is able to promote a decrease in GFAP expression [15] and an increase in glutamate uptake, contributing to neuroprotection in vivo [16]. Furthermore, by using micropatterned grooved scaffolds, mature astrocytes were found to revert into radial glia-like cells and consequently to a more pro-regenerative phenotype [17].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, sterilized PLLA fiber scaffolds were coated with fibronectin (10 μg/mL), since we previously observed astrocytes strongly adhering to fibronectin coated fibers [34]. However, in experiments presented here, we observed astrocyte adhesion to be less at the AFFT interface, so a different coating procedure was devised.…”
Section: Methodsmentioning
confidence: 86%
“…Previously, our laboratory has shown that astrocytes cultured on aligned fibers have an aligned cytoskeleton, while the cytoskeletons of astrocytes cultured on PLLA films have no preferential orientation [34]. Similarly, others demonstrated aligned presentation of fibronectin produced by astrocytes cultured on adsorbed laminin patterns [39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation